2016
DOI: 10.20892/j.issn.2095-3941.2016.0080
|View full text |Cite
|
Sign up to set email alerts
|

Human endogenous retroviruses and cancer

Abstract: Human endogenous retroviruses (HERVs) are retroviruses that infected human genome millions of years ago and have persisted throughout human evolution. About 8% of our genome is composed of HERVs, most of which are nonfunctional because of epigenetic control or deactivating mutations. However, a correlation between HERVs and human cancer has been described and many tumors, such as melanoma, breast cancer, germ cell tumors, renal cancer or ovarian cancer, express HERV proteins, mainly HERV-K (HML6) and HERV-K (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 54 publications
(55 reference statements)
0
49
0
5
Order By: Relevance
“…ERVs constitute 8% and 10% of human and mouse genomes, respectively (Waterston, Lindblad-Toh et al, 2002; Lander, Linton et al, 2001) and are remnants of ancient retrovirus infection of the germline. Importantly, some of these elements encode a functional RT and increased expression of endogenous retroviruses is observed in several conditions, including cancer and virus infections (Argaw-Denboba, Balestrieri et al, 2017; Johanning, Malouf et al, 2017; Assinger, Yaiw et al, 2013; Mangeney, Pothlichet et al, 2005; Gonzalez-Cao, Iduma et al, 2016). Increased expression of functional RT encoded by ERVs and subsequent generation of single stranded DNA could account for the cytoplasmic DNA observed in ATM deficient conditions.…”
Section: Resultsmentioning
confidence: 99%
“…ERVs constitute 8% and 10% of human and mouse genomes, respectively (Waterston, Lindblad-Toh et al, 2002; Lander, Linton et al, 2001) and are remnants of ancient retrovirus infection of the germline. Importantly, some of these elements encode a functional RT and increased expression of endogenous retroviruses is observed in several conditions, including cancer and virus infections (Argaw-Denboba, Balestrieri et al, 2017; Johanning, Malouf et al, 2017; Assinger, Yaiw et al, 2013; Mangeney, Pothlichet et al, 2005; Gonzalez-Cao, Iduma et al, 2016). Increased expression of functional RT encoded by ERVs and subsequent generation of single stranded DNA could account for the cytoplasmic DNA observed in ATM deficient conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, products of the envelope genes, i.e. syncytins, which are normally restricted to the placenta, have been identified in human malignancies, and it has been suggested that syncytin-mediated cell fusion events play a role in the transformation and metastasis process [ 21 , 24 , 33 , 46 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The global hypomethylation of the genome observed in many tumors is likely to explain the reactivation of HERV transcription, usually silenced by CpG methylation of the LTRs ( Stengel et al, 2010 ). Among the possible oncogenic mechanisms, HERV-K could participate to cell transformation by insertional mutagenesis, through its rec and np9 oncogenic proteins, or even by modulating the immune response ( Gonzalez-Cao et al, 2016 ). However, even if HERVs are released as particles (which is rarely the case), they remain non-infectious ( Denner, 2016 ).…”
Section: Study Of Endogenous Retroviruses In Swine Melanomamentioning
confidence: 99%